Kapasitas Adaptasi Terhadap Kerentanan dan Bencana Perubahan Iklim di Tambak Lorok Kelurahan Tanjung Mas Semarang - Kumalasari, Novia Riska (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
For overall the coastal area is one of area that has an important role and it is source of life for coastal communities. Crucial issues about the impact of climate change such as sea level rises would cause a vulnerability in coastal areas that have an impact on the infrastructure damage and threaten the socio-economic conditions the people. One of the settlements are experiencing the impact of climate change is happening in Tambak Lorok Village Tanjung Mas Semarang, District of North. Tambak Lorok are coastal areas in Semarang, which has a very poor condition. Settlements are more vulnerable to climate change needs adaptive capacity. Therefore The purpose of this research is to find out the adaptive capacity to the existence of vulnerabilities and disaster rob as a result of climate change that occurred in the coastal settlements Tambak Lorok, Semarang. The research using kuantitative approach. In the adaptive capacity indicates that the level of household has a high adaptive capacity while adaptive capacity at the community level andÂ city level was at a moderate level. In adaptive capacity assessment identified by indicator ability of stakeholder, finance, technology, performance, and management on each stakeholder, that are household, community, and city level.